ANALISIS KOMPARASI RELEVANSI NILAI INFORMASI AKUNTANSI SEBELUM DAN SESUDAH ADOPSI IFRS DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2009-2014) - Fajar Dewantoro; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
This study aimed to test whether there is an increase in the value relevance of accounting information after the adoption of IFRS in Indonesia. The value relevance of accounting information can be seen on the effect of earnings per share, book value of equity, operating cash flows, and goodwill in the decision-making of investors as reflected in the stock price.This research was an empirical study with purposive sampling technique in data collection. Data were obtained from secondary data manufacturing company’s financial statements during period 2009 through 2014.The sample consisted of 13 companies with total of 78 data during this before and after IFRS period. The data were analyzed using multiple regression analysis and chow test analysis The result of this study showed that there were an increasing in the value relevance of accounting information after adoption of IFRS in Indonesia. This chow test result showed that there were no regression model deferences between the value relevance of accounting information before and after the adoption of IFRS in Indonesia.